Mengidentifikasi Senyawa Flavonoid Menggunakan Limbah Kulit Bawang Merah (Allium cepa.L) dengan Spektrofotometri UV-Vis - Bunga Regista Cahyani; Nabilla Putri Nurizha; Reza Akbar Fadilla; Ermi Abriyani; Andrian Supriatna; Febriani Dwi Anzaini (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Onion skin (Allium cepa L.) waste from the household industry is largely unutilized. This is unfortunate because shallot skin contains many compounds that can be utilized, one of which is flavonoids which have potential as antioxidants. In this study, methanol was used as a solvent to extract shallot skin. Antioxidant activity test was conducted using CR (Cerium (IV) Sulfate) method. From the UV-Vis spectra, it can be concluded that this flavonoid belongs to the flavonol group and is seen in the wavelength range between 240-285 nm (band II) and 300-550 nm (band I).